Clinical and sociodemographic factors associated with oral health knowledge, attitude, and practices of adolescents in Nigeria (2020)
The institution of appropriate oral health promotion programs targeted at adolescents in schools in developing countries requires baseline information on their oral health knowledge, attitude, and practices as well as associated factors influencing it, which are unknown. This study assessed clinical and sociodemographic factors associated with oral health knowledge, attitude, and practices of adolescents in Ibadan, Nigeria. Two-thousand and ninety-seven students aged 12-18 years were recruited from 30 randomly selected secondary schools in a cross-sectional study conducted in Ibadan, Nigeria. Data were obtained through a questionnaire on oral health knowledge, attitude, and practices, and sociodemographic characteristics. Oral examination was conducted to assess the clinical oral condition of the adolescents. Data were analyzed with SPSS. The higher the percentage scores, the better the oral health knowledge, attitude, and practices, and overall awareness of oral health. The oral health knowledge score ranged from 0% to 60%; mean oral health knowledge score was 15.1% (±6.6%). The oral health attitude score ranged from 0% to 91.3%; mean oral health attitude score was 44.5% (± 14.3%). The oral health practices score ranged from 0% to 88.9%, and mean oral health practices score was 42.5% (± 13.8%). The mean oral health knowledge, attitude, and practices score was 43.8% (± 11.4%). A total of 1537 (73.3%) participants had unhealthy periodontium and 98 (4.7%) had dental caries. Students who were 12-15 years (odds ratio = 1.7, 95% confidence interval = 1.42.0, p < 0.001), females (odds ratio = 1.2, 95% confidence interval = I.0-I.5, p = 0.024), offspring of skilled workers (odds ratio = 1.5, 95% confidence interval = I.I-2.0, p = 0.010), previously educated about oral health (odds ratio = 1.3, 95% confidence interval = I.0-I.7, p = 0.023), consulted the dentist (odds ratio = 1.9, 95% confidence interval = I.2-3.I, p = 0.009), or had unhealthy periodontal condition (odds ratio = I.2, 95% confidence interval = I.0-I.5, p = 0.042) were more likely to have higher oral health knowledge, attitude, and practices scores or awareness than others. Better knowledge, attitude, and practices score was associated with younger age group, higher occupational class, previous oral health education, dental consultation, and having unhealthy periodontal condition